Fashion show (2001)
Diseño de interior de una tienda de Giorgio Armani en Milán, Italia, por Claudio Silvestrin
Keywords: ITALIA; MILAN; DISEÑO; DISEÑO DE INTERIORES; TIENDAS; LOCALES COMERCIALES; SILVESTRIN, CLAUDIO